CONSERVATISM AND THE COST OF EQUITY CAPITAL: A MULTI-DIMENSIONAL MEASUREMENT APPROACH - Gamaliel, Hendrik; Sugiri, Slamet (Journal of Indonesian Economy and Business, 2013)
Conservatism is a permanent phenomenon and issue in the accounting practice. It has beendeveloping in two forms, ex ante and ex post, measured in various waysâthe accruals,valuation model, and book-to-market measures. Prior studies document inconclusive findingson the association between conservatism and the cost of equity capital. These inconsistentfindings motivate us to examine whether the various measures of conservatism have differenteffects on the relationship between conservatism and the cost of equity capital. Wefind that the accruals measure explains the relationship, while the valuation model andbook-to-market measures do not. Our findings suggest that different measures of conservatismrelate differently to different articulations. Researchers, therefore, should be cautious ininterpreting the relationship between conservatism and the cost of equity capital.Keywords: ex ante and ex post conservatism, cost of equity capital, various measures ofconservatism